Lecturer’s perspective on self-efficacy towards research: ‘push or not to push’ - Velu, Jeya; Sheikh Ahmad, Ismail; Abdul Rahman, Zainurin (2011)
Lecturers in teacher training institute are encouraged to conduct research and are given the opportunities to present the research findings in conferences or to publish them in journals. However, the number of articles produced yearly is not promising compared to the number of lecturers in the institution. This duty seeks to examine the factors which affect lecturer’s self-efficacy towards research activities. A case study was conducted in a teacher training institute, involving four lectures who have more than 20 years of teaching experiences. These lectures were interviewed using semi structured interview. Through phenomenological approach analysis, five salient factors were discovered from these interviews, namely, subject matter expertise, motivation, positive environment, interest and personal strength. This article discusses the nature of these five factors and their implications on the willingness of lecturers to be involved in research activities. This article also provides some measures that can be taken to enhance the lecturers’ self –efficacy towards research.